Data base of Characterization of self-reported sleep quality in male and female trained amateur triathletes: a descriptive study - Luiz Vieira da Silva Neto; Tatiana Albuquerque Melo Kramer; Gloria Maria Alves Trajano; Luiz José Frota Solon Júnior (Universidad de Costa Rica, 2024)
Sleep quality is a determining factor for the performance and health of athletes in general. The aim of the present study was to characterize the sleep quality in male and female trained amateur triathletes aged 20 to 59 years. A survey was conducted with 151 trained amateur triathletes, 108 male (38.6 ±8.1 years, triathlon training experience 5.8 ±4.3years, training frequency 6.3 ±0.9 days per week) and 43 female (39.3 ±7.6 years, triathlon training experience 4.8 ±3.3years, training frequency 6.5 ±0.6 days per week). The sleep quality was measured using the Pittsburgh Sleep Quality Index-Br (PSQI-Br), total values below 05 points indicate good sleepers, and values equal to or greater than 05 points indicate poor sleepers. Data from the subscales were analyzed using absolute and relative frequency. The other data in order to characterize sleep quality were analyzed with median, mean, standard deviation, standard error, and 95% Confidence Interval of mean.  Male and female triathletes have poor sleep quality (values equal or greater than 05 points), that can have negative effects on health and performance.  In conclusion, all triathletes regardless of gender and age group have poor sleep quality.